1Dosen Pembimbing Pertama 2Dosen Pembimbing Kedua 3Yunarto, Holy Icun & Martinus Getty Santika. 2005. Business Concepts Implementation Series in Inventory Management. Jakarta: PT Elex Media Komputindo. 1 | P a g e ANALISIS IMPLEMENTASI JUST IN TIME DALAM MENINGKATKAN EFEKTIVITAS PRODUKSI GARMEN (STUDI KASUS PADA SUBSIDIARY COMPANY PAN 12 PT. PAN BROTHERS Tbk) - Febrianto Andi Rahmawan; Poniman Poniman; Suharmanto Suharmanto (JOBS (Jurnal Of Business Studies), 2016)
The purpose of this study is to analyze and describe the implementation of the just intime in the production process of the garments on the Subsidiary Company PAN 12PT. Pan Brothers Tbk in Boyolali, Central Java and to know how the implementationof the just in time in relation to improving the effectiveness of the production. To findout how much the company achieved production effectiveness, in this study usedmeasurement method by using the calculation of the Manufacturing CycleEffectiveness (MCE) by dividing the non-value added activities and value addedactivities, from the calculation of the MCE can be the measurement of theeffectiveness of the company where the company has a value of 100% means theMCE has the ideal production effectiveness, while less than 100% then neededimprovement. The result of this study, the calculation of the Manufacturing CycleEffectiveness (MCE) generated in the implementation of the just in time of 66,19%.From that result, companies can make improvements by reducing or eliminating nonvalue added activities to increase the value of the MCE, with the result thateffectiveness of production can be achieved. Based on the results of the analysisthere is a difference between the Manufacturing Cycle Effectiveness (MCE) betweenin advance of improvements of 66.19% and following improvement of 79,19%.Improvement attempts by reducing or eliminating non value added activities capableof improving the Manufacturing Cycle Effectiveness (MCE) of 13% (79,19%-66,19%) than in advance of improvements in the implementation of the just in time.